2013
DOI: 10.1097/dbp.0b013e3182a509fb
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-related Behaviors of US- and Non-US-born Parents and Children in Low-income Households

Abstract: Objective To examine differences in obesity-related behaviors by parental US born status among low-income, minority families participating in Healthy Habits, Happy Homes, an intervention trial to improve household routines for childhood obesity prevention. Evidence suggests lower obesity risk among adult immigrants, but research is inconclusive regarding the influence of having a non-US born parent on childhood obesity. Method We sampled 57 US born and 64 non-US born families of children ages 2–5.9 years liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…This finding is important because previous studies indicate that children living in households with regular family routines (e.g. regularly eating meals as a family) are at lower risk of obesity than those who do not have household routines (10)(11)(12) . Although it is essential that parents recognize the importance of healthful behaviours, parents need to have the self-efficacy to make changes to the home and family environment that support children's healthy eating and PA (27,28) .…”
Section: Discussionmentioning
confidence: 91%
“…This finding is important because previous studies indicate that children living in households with regular family routines (e.g. regularly eating meals as a family) are at lower risk of obesity than those who do not have household routines (10)(11)(12) . Although it is essential that parents recognize the importance of healthful behaviours, parents need to have the self-efficacy to make changes to the home and family environment that support children's healthy eating and PA (27,28) .…”
Section: Discussionmentioning
confidence: 91%
“…Cespedes, McDonald, Haines, Bottino, and Taveras () examined obesity‐related behaviors in urban, low‐income, and non‐US‐ and US‐born racial/ethnic minority preschool‐age children (34% Black, 52% Hispanic) and found that time spent in active play was lower among children whose parents were born outside the United States than among those whose parents were born in United States, after adjusting for parental education.…”
Section: Resultsmentioning
confidence: 99%
“…Findings from studies included in this review elucidated multilevel factors at various levels in the social–ecological model that influence preschool‐age children's PA levels and behaviors. At the individual level, factors associated with differing levels of PA include SES and the child's sex (Annesi, Smith, & Tennant, ; Bagley et al., ; Cespedes et al., ; Chuang, Sharman, Skala, & Evans, ; Kumanyika & Grier, ; Montgomery et al., ; O'Connor et al., ; Pate et al., ; Salmon et al., ; Sisson et al., ; Suen et al., ; Vale et al., ; Van Cauwenberghe et al., ). At the individual level, some factors suggest that the lack of PA may have to do with lack of access or insufficient family resources to make PA a priority (e.g., SES, family structure), while other factors suggest parental values come into play (child's sex and cultural context).…”
Section: Discussionmentioning
confidence: 99%
“…The latter finding is somewhat at variance with the established direct correlation between lower socioeconomic/educational indices and the prevalence of obesity in native-born US residents. Explanations proffered in literature for this "immigrant paradox" include a 'healthy immigrant' effect (HIE), the protective influence of strong social networks and family ties, and even a reporting bias (Cespedes et al, 2013). The observed lower risk of obesity among US immigrants is all the more interesting in the light of increasing rates of obesity in countries like Mexico that account for a high proportion of immigrants to the US (Ogden et al, 2012).…”
Section: Introductionmentioning
confidence: 99%